Delayed Medullar Syndrome after Aneurysmal Subarachnoid Haemorrhage: A Case report of Cystic Arachnoiditis! - Silva, N. (Centauro S.r.l., 2007)
We described a case of chronic spinal cystic arachnoiditis after subarachnoid haemorrhage in a 54-year-old woman with a ruptured vertebral artery aneurysm treated by coils. At three months she complained of lumbar pain. At twelve months she presented lower limbs paresthesia then a rapidly bilateral motor deficit. MR showed a spinal arachnoiditis with two compressive cysts. Surgical decompression was inefficient and after three months spinal compression symptoms worsened and MR signs were unchanged.